THE INFLUENCE OF MERONCE AND COLLAGE ACTIVITIES ON THE RESILIENCE OF CLASS B RA CHILDREN IN RA MUSLIMAT AL-WASHLIYAH THE CITY OF THE HIGH CLUB - Tri Ananda Putri; Asih Menanti; Amanah Surbakti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Early childhood resilience is a process of assistance by PAUD educators to prepare early childhood to be able to face vulnerabilities and challenges, avoid setbacks, so that they are successful in all areas of life now and in the future, including being ready to adapt to elementary school. The expected child is an emotionally healthy child who can face vulnerabilities, challenges, and avoid setbacks. This study aims to determine the effect of grouping activities and collage activities on the resilience of children aged 5-6 years at RA Muslimat Al-Washliyah Tebing Tinggi City. This study used the Quasi-Experimental method with two forms of activities, namely collage activities and grouping activities. Where each activity is carried out six times, starting from the easiest activities to the most difficult activities. The data collection instrument used was a questionnaire about 18 items of child resilience. Data analysis was performed by data description and hypothesis testing using the Wilcoxon Signed Ranks Test. The results of the data analysis showed that: 1) The child's resilience score at the pretest of the Meronce activity total score was 232, the average was 38.67, the maximum was 41, and the minimum was 37. The child's resilience score at the posttest was the total score of 343, the average 57.17, maximum 58, minimum 56. 2) Resilience score of children during collage activities during pretest total score 343, average 57.17, maximum 58, minimum 56. Resilience score of children during posttest collage activities total score 353, average - average 58.83, maximum 60, minimum 57. 3) There is an effect of meronce activities on increasing children's resilience with a significance of 0.001 <0.05. 4) There is an effect of collage activities on increasing children's resilience with a significance of 0.002 <0.05. It can be concluded that there is an effect of collage and group activities on the resilience of children aged 5-6 years at RA Muslimat Al-Washliyah, Tebing Tinggi City.